Streetlights positively affect the presence of an invasive grass species. Issue 15 (10th July 2021) - Murphy, Shannon M.; Vyas, Dhaval K.; Hoffman, Jennifer L.; Jenck, Clara S.; Washburn, Brooke A.; Hunnicutt, Kelsie E.; Davidson, Angie; Andersen, Jasmine M.; Bennet, Rachel K.; Gifford, Amarin; Herrera, Mia; Lawler, Braelynn; et al.
Abstract: Anthropogenic disturbances associated with urban ecosystems can create favorable conditions for populations of some invasive plant species. Light pollution is one of these disturbances, but how it affects the growth and establishment of invasive plant populations is unknown. Cheatgrass ( Bromus tectorum ) is a problematic invasive species where it has displaced native grassland communities in the United States, but to our knowledge, there have been no studies of the ecological factors that affect cheatgrass presence in urban ecosystems. We conducted field surveys in urban alleys in Denver, Colorado, to compare the presence of cheatgrass at sites with and without artificial light at night (hereafter artificial light) from streetlights. These streetlights are mounted on utility poles, which cause ground disturbance when installed in alleys; we were able to test the independent effect of poles on cheatgrass establishment because not all poles have streetlights on them. We found that cheatgrass was positively associated with the presence of streetlights and to a lesser extent poles. In addition to cheatgrass, we also found that other plants were positively associated with the presence of both poles and streetlights. Our results suggest that artificial light may benefit the occurrence of cheatgrass and other plant species in urban settings. While invasive populations of cheatgrass in wild habitats attract the most attention from managers, we suggest more consideration for this grass in urban environments where its growth and establishment benefit from anthropogenic changes. Abstract : We have found that light pollution facilitates an invasive plant species, cheatgrass. Ours is the first study to document the effect of this global change driver, artificial light at night, on this important invasive plant species.